2018
DOI: 10.1242/jcs.222034
|View full text |Cite
|
Sign up to set email alerts
|

An interaction network between the SNARE VAMP7 and Rab GTPases within a ciliary membrane-targeting complex

Abstract: The Arf4-rhodopsin complex (mediated by the VxPx motif in rhodopsin) initiates expansion of vertebrate rod photoreceptor ciliaderived light-sensing organelles through stepwise assembly of a conserved trafficking network. Here, we examine its role in the sorting of VAMP7 (also known as TI-VAMP)an R-SNARE possessing a regulatory longin domain (LD)into rhodopsin transport carriers (RTCs). During RTC formation and trafficking, VAMP7 colocalizes with the ciliary cargo rhodopsin and interacts with the Rab11-Rabin8-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 110 publications
1
12
0
Order By: Relevance
“…The presence of Longin domain is broadly shared by vesicle trafficking proteins [ 48 , 49 ]. These Longin domain-containing proteins transport specific cargos and target their membrane localization in support of cilia outgrowth, which is impaired when protein dysfunctions occur [ 11 , 50 ]. Interestingly, the R404Q mutation was initially identified from human patients with neural tube defects, a severe neurological deficit due to the failure of neural tube closure during embryonic development, and Seo et al [ 47 ] showed that Fuz R404Q mutant prevents cilia elongation and directional cell movements.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Longin domain is broadly shared by vesicle trafficking proteins [ 48 , 49 ]. These Longin domain-containing proteins transport specific cargos and target their membrane localization in support of cilia outgrowth, which is impaired when protein dysfunctions occur [ 11 , 50 ]. Interestingly, the R404Q mutation was initially identified from human patients with neural tube defects, a severe neurological deficit due to the failure of neural tube closure during embryonic development, and Seo et al [ 47 ] showed that Fuz R404Q mutant prevents cilia elongation and directional cell movements.…”
Section: Discussionmentioning
confidence: 99%
“…and Syntaxin3 [23,26,27], explaining the observed massive accumulation of unfused vesicles in cc2d2a-/-zebrafish PRs.…”
Section: The Connecting Cilium-at the Crossroads Between Inner And Oumentioning
confidence: 91%
“…Rabin8 is recruited to the developing vesicle and leads to the formation of the Rab11-Rabin8-Rab8 module. The Rab11-Rabin8-Rab8 module recruits the SNARE component VAMP7 into the budding secretory vesicles, called rhodopsin transport carriers (RTCs) (Deretic et al, 2004 ; Wang and Deretic, 2014 ), making them competent for fusion with the plasma membrane near the base of the cilium containing the partner SNARE components syntaxin 3 and SNAP25 (Kandachar et al, 2018 ).…”
Section: Intrinsic Membrane Protein Compartmentalization Within the Cmentioning
confidence: 99%